House, home and transforming energy in a cold climate. (18th November 2016) - Webb, Janette; Hawkey, David; Mccrone, David; Tingey, Margaret
Abstract : Warm homes are fundamental to a sense of personal security and citizenship, but many lowincome families and households struggle to pay their energy bills, and energy prices are caught up in the politics of welfare and climate change. Our research uses a sociological perspective to investigate the experiences of low-income households, on a Glasgow housing estate, living through a major renovation programme to insulate homes and install community heating. The Housing Association's aim was to combine amelioration of fuel poverty with reduced greenhouse gas emissions. We examine the complex results from the renovation, which indicate that the UK economistic model of households as primarily consumers limited, rather than facilitated, the achievement of desired co-benefits for welfare and environment. We show the centrality of personal and domestic relationships to the future of affordable, secure and clean energy. We suggest that social scientists have an important contribution to public understanding of connections between families and relationships, localities and the politics of energy and environment.